EFFECT OF COST INCREMENT DISTRIBUTION PATTERNS ON THE PERFORMANCE OF JIT SUPPLY CHAIN - Ayu Bidiawati J.R; Noor Ajian Mohd Lair (Institute of Research and Community Outreach - Petra Christian University, 2008)
Cost is an important consideration in supply chain (SC) optimisation. This is due to emphasis placed on cost reduction in order to optimise profit. Some researchers use cost as one of their performance measures and others propose ways of accurately calculating cost. As product moves across SC, the product cost also increases. This paper studied the effect of cost increment distribution patterns on the performance of a JIT Supply Chain. In particular, it is necessary to know if inventory allocation across SC needs to be modified to accommodate different cost increment distribution patterns. It was found that funnel is still the best card distribution pattern for JIT-SC regardless the cost increment distribution patterns used.